TiO2/LaFeO3 Composites for the Efficient Degradation of Benzoic Acid and Hydrogen Production - Isabella Natali Sora; Benedetta Bertolotti; Renato Pelosato; Andrea Lucotti; Matteo Tommasini; Marica Muscetta (Molecules)
LaFeO3/TiO2 composites were prepared in the range 0–12.2 wt% of LaFeO3, characterized, and tested for both benzoic acid (BA) and 4-methoxycinnamic acid (MCA) degradation in aqueous solution, and hydrogen evolution. The preparation method was via ball-milling without thermal treatment. The composite materials presented agglomerates of LaFeO3 with an average size from 1 to 5 μm, and the TiO2 powder was well dispersed onto the surface of each sample. They showed varying activities for BA degradation depending on composition and light wavelength. The 6.2 wt% and 12.2 wt%-LaFeO3/TiO2 composites exhibited the highest activity under 380–800 nm light and could degrade BA in 300 min at BA concentration 13.4 mg L−1 and catalyst 0.12 g L−1. Using a 450 nm LED light source, all composites degraded less than 10% of BA, but in the presence of H2O2 (1 mM) the photocatalytic activity was as high as 96% in <120 min, 6.2 wt%-LaFeO3/TiO2 composite being the most efficient sample. It was found that in the presence of H2O2, BA degradation followed first order kinetic with a reaction rate constant of 4.8 × 10−4 s−1. The hydrogen production rate followed a classical volcano-like behavior, with the highest reactivity (1600 μmol h−1g−1 at 60 °C) in the presence of 3.86%wt- LaFeO3/TiO2. It was also found that LaFeO3/TiO2 exhibited high stability in four recycled tests without losing activity for hydrogen production. Furthermore, a discussion on photogenerated charge-carrier transfer mechanism is briefly provided, focusing on lacking significant photocatalytic activity under 450 nm light, so p-n heterojunction formation is unlikely.